Pengaruh Komonukasi Interpersonal terhadap Motivasi Belajar PAI Siswa - Restian; La Hadisi; Sitti Aisyah Mu’min; Dalman (Tarbiyatul Akhyar: Jurnal Pendidikan, 2025)
This research aims to examine interpersonal communication on students' motivation to learn Islamic religious education at SMPN 1 Lasolo. This research is quantitative research with descriptive methods. Data collection was carried out by observation and questionnaires distributed to 76 samples which were used as research objects. Research data was analyzed using a simple linear regression formula. The results of this research show that interpersonal communication has an influence on students' Islamic religious education learning motivation with a contribution of 25.6% while the remainder (74.4%) is influenced by other variables. So the hypothesis accepted in this research is the alternative hypothesis (H1: β ≠ 0), namely that there is an influence of interpersonal communication on students' motivation to learn Islamic religious education.